The Dynamics of the Free-Rider Problem in Takeovers - Harrington, Joseph E.; Prokop, Jacek (Review of Financial Studies, 1993)
We explore the dynamics of a takeover bid. In contrast to preceding models, if the initial takeover bid is unsuccessful a raider is allowed to make a new tender offer in order to try and secure the remaining shares. Numerical analysis shows that the raider’s tender offer rises over time as he accumulates more shares. The anticipation of a higher tender offer in the future makes shareholders more inclined to hold their shares and forces the raider to offer a higher premium than is predicted by static theories. As the time between tender offers goes to zero, we show analytically that the expected profit from engaging in a takeover goes to zero.